TINGKAT PENGETAHUAN DAN SIKAP SISWA-SISWI GLOBAL PRIMA MEDAN MENGENAI INFEKSI MENULAR SEKSUAL TAHUN 2015 - Cicilia Rosalyn Sitorus; Boyke Martin (Universitas Prima Indonesia, 2019)
In many countries, sexually transmitted infections (STIs) continue to be a health, social, and financial problem. It has been proposed that the introduction of extensive counseling programs would reduce or maintain a reasonably stable STI incidence in many countries. Despite this, STI prevalence remains high in most countries. Although children can contract STIs from their mothers, most STI patients are adolescents aged between 15 and 29 years. The relatively low level of knowledge among adolescents is one of the factors contributing to the high frequency of STIs, especially in the adolescent age group. This will eventually have an impact on adolescents' attitudes about STIs. This study aimed to determine the knowledge and attitude of Global Prima Medan high school students regarding STIs. This research method is descriptive, using a cross-sectional approach and survey method. All students of SMA Global Prima Medan constituted the study population. There were 135 samples in this study, and the relative accuracy level (d) was set at 0.1. A stratified random sampling strategy was used for the sampling process. Questionnaires were used for data collection, and descriptive statistics were used for data analysis. The results of the assessment of high school students in Global Prima Medan regarding their knowledge and attitude about STIs showed that most fell into the poor category (53.3%) for knowledge and the fair category (54.1%) for attitude.